NMR Spectroscopy of supramolecular chemistry on protein surfaces - Bayer, Peter; Matena, Anja; Beuck, Christine (Beilstein Journal of Organic Chemistry, 2020)
As one of the few analytical methods that offer atomic resolution, NMR spectroscopy is a valuable tool to study the interaction of proteins with their interaction partners, both biomolecules and synthetic ligands. In recent years, the focus in chemistry has kept expanding from targeting small binding pockets in proteins to recognizing patches on protein surfaces, mostly via supramolecular chemistry, with the goal to modulate protein–protein interactions. Here we present NMR methods that have been applied to characterize these molecular interactions and discuss the challenges of this endeavor.
Keywords: molecular recognition; NMR; protein ligand interaction; protein surfaces; supramolecular chemistry

(untitled) - Arkin, M. R.; Tang, Y.; Wells, J. A. (Chem. Biol., 2014)

(untitled) - Uhlenheuer, D. A.; Petkau, K.; Brunsveld, L. (Chem. Soc. Rev., 2010)

(untitled) - Keskin, O.; Ma, B.; Nussinov, R. (J. Mol. Biol., 2005)

(untitled) - Perkins, J. R.; Diboun, I.; Dessailly, B. H.; Lees, J. G.; Orengo, C. (Structure, 2010)

(untitled) - Fokkens, M.; Schrader, T.; Klärner, F.-G. (J. Am. Chem. Soc., 2005)

(untitled) - Bier, D.; Rose, R.; Bravo-Rodriguez, K.; Bartel, M.; Ramirez-Anguita, J. M.; Dutt, S.; Wilch, C.; Klärner, F.-G.; Sanchez-Garcia, E.; Schrader, T.; Ottmann, C. (Nat. Chem., 2013)

(untitled) - Trusch, F.; Kowski, K.; Bravo-Rodriguez, K.; Beuck, C.; Sowislok, A.; Wettig, B.; Matena, A.; Sanchez-Garcia, E.; Meyer, H.; Schrader, T.; Bayer, P. (Chem. Commun., 2016)

(untitled) - Sinha, S.; Lopes, D. H. J.; Du, Z.; Pang, E. S.; Shanmugam, A.; Lomakin, A.; Talbiersky, P.; Tennstaedt, A.; McDaniel, K.; Bakshi, R.; Kuo, P.-Y.; Ehrmann, M.; et al. (J. Am. Chem. Soc., 2011)

(untitled) - Prabhudesai, S.; Sinha, S.; Attar, A.; Kotagiri, A.; Fitzmaurice, A. G.; Lakshmanan, R.; Ivanova, M. I.; Loo, J. A.; Klärner, F.-G.; Schrader, T.; Stahl, M.; Bitan, G.; et al. (Neurotherapeutics, 2012)

(untitled) - Acharya, S.; Safaie, B. M.; Wongkongkathep, P.; Ivanova, M. I.; Attar, A.; Klärner, F.-G.; Schrader, T.; Loo, J. A.; Bitan, G.; Lapidus, L. J. (J. Biol. Chem., 2014)

(untitled) - Lopes, D. H. J.; Attar, A.; Nair, G.; Hayden, E. Y.; Du, Z.; McDaniel, K.; Dutt, S.; Bandmann, H.; Bravo-Rodriguez, K.; Mittal, S.; Klärner, F.-G.; Wang, C.; et al. (ACS Chem. Biol., 2015)

(untitled) - Zheng, X.; Liu, D.; Klärner, F.-G.; Schrader, T.; Bitan, G.; Bowers, M. T. (J. Phys. Chem. B, 2015)

(untitled) - Talbiersky, P.; Bastkowski, F.; Klärner, F.-G.; Schrader, T. (J. Am. Chem. Soc., 2008)

(untitled) - Attar, A.; Ripoli, C.; Riccardi, E.; Maiti, P.; Li Puma, D. D.; Liu, T.; Hayes, J.; Jones, M. R.; Lichti-Kaiser, K.; Yang, F.; Gale, G. D.; Tseng, C.-H.; et al. (Brain, 2012)

(untitled) - Herzog, G.; Shmueli, M. D.; Levy, L.; Engel, L.; Gazit, E.; Klärner, F.-G.; Schrader, T.; Bitan, G.; Segal, D. (Biochemistry, 2015)

(untitled) - Lump, E.; Castellano, L. M.; Meier, C.; Seeliger, J.; Erwin, N.; Sperlich, B.; Stürzel, C. M.; Usmani, S.; Hammond, R. M.; von Einem, J.; Gerold, G.; Kreppel, F.; et al. (eLife, 2015)

(untitled) - Attar, A.; Chan, W.-T. C.; Klärner, F.-G.; Schrader, T.; Bitan, G. (BMC Pharmacol. Toxicol., 2014)

(untitled) - Bier, D.; Mittal, S.; Bravo-Rodriguez, K.; Sowislok, A.; Guillory, X.; Briels, J.; Heid, C.; Bartel, M.; Wettig, B.; Brunsveld, L.; Sanchez-Garcia, E.; Schrader, T.; et al. (J. Am. Chem. Soc., 2017)

(untitled) - Kimura, Y.; Saito, N.; Hanada, K.; Liu, J.; Okabe, T.; Kawashima, S. A.; Yamatsugu, K.; Kanai, M. (ChemBioChem, 2015)

(untitled) - McGovern, R. E.; Fernandes, H.; Khan, A. R.; Power, N. P.; Crowley, P. B. (Nat. Chem., 2012)

(untitled) - McGovern, R. E.; McCarthy, A. A.; Crowley, P. B. (Chem. Commun., 2014)

(untitled) - McGovern, R. E.; Snarr, B. D.; Lyons, J. A.; McFarlane, J.; Whiting, A. L.; Paci, I.; Hof, F.; Crowley, P. B. (Chem. Sci., 2015)

(untitled) - Rennie, M. L.; Doolan, A. M.; Raston, C. L.; Crowley, P. B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Rennie, M. L.; Fox, G. C.; Pérez, J.; Crowley, P. B. (Angew. Chem., Int. Ed., 2018)

(untitled) - Alex, J. M.; Rennie, M. L.; Engilberge, S.; Lehoczki, G.; Dorottya, H.; Fizil, Á.; Batta, G.; Crowley, P. B. (IUCrJ, 2019)

(untitled) - Alex, J. M.; Rennie, M. L.; Volpi, S.; Sansone, F.; Casnati, A.; Crowley, P. B. (Cryst. Growth Des., 2018)

(untitled) - Doolan, A. M.; Rennie, M. L.; Crowley, P. B. (Chem. – Eur. J., 2018)

(untitled) - Mummidivarapu, V. V. S.; Rennie, M. L.; Doolan, A. M.; Crowley, P. B. (Bioconjugate Chem., 2018)

(untitled) - Beshara, C. S.; Jones, C. E.; Daze, K. D.; Lilgert, B. J.; Hof, F. (ChemBioChem, 2010)

(untitled) - Tabet, S.; Douglas, S. F.; Daze, K. D.; Garnett, G. A. E.; Allen, K. J. H.; Abrioux, E. M. M.; Quon, T. T. H.; Wulff, J. E.; Hof, F. (Bioorg. Med. Chem., 2013)

(untitled) - Allen, H. F.; Daze, K. D.; Shimbo, T.; Lai, A.; Musselman, C. A.; Sims, J. K.; Wade, P. A.; Hof, F.; Kutateladze, T. G. (Biochem. J., 2014)

(untitled) - Ali, M.; Daze, K. D.; Strongin, D. E.; Rothbart, S. B.; Rincon-Arano, H.; Allen, H. F.; Li, J.; Strahl, B. D.; Hof, F.; Kutateladze, T. G. (J. Biol. Chem., 2015)

(untitled) - Buldenko, V. M.; Trush, V. V.; Kobzar, O. L.; Drapailo, A. B.; Kalchenko, V. I.; Vovk, A. I. (Bioorg. Med. Chem. Lett., 2019)

(untitled) - Akermi, N.; Mkaouar, H.; Kriaa, A.; Jablaoui, A.; Soussou, S.; Gargouri, A.; Coleman, A. W.; Perret, F.; Maguin, E.; Rhimi, M. (Chem. Commun., 2019)

(untitled) - Vovk, A. I.; Kononets, L. A.; Tanchuk, V. Y.; Cherenok, S. O.; Drapailo, A. B.; Kalchenko, V. I.; Kukhar, V. P. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Shinde, M. N.; Barooah, N.; Bhasikuttan, A. C.; Mohanty, J. (Chem. Commun., 2016)

(untitled) - Wang, Z.; Tao, S.; Dong, X.; Sun, Y. (Chem. – Asian J., 2017)

(untitled) - Xu, Z.; Jia, S.; Wang, W.; Yuan, Z.; Ravoo, B. J.; Guo, D.-S. (Nat. Chem., 2019)

(untitled) - Martos, V.; Bell, S. C.; Santos, E.; Isacoff, E. Y.; Trauner, D.; de Mendoza, J. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Gordo, S.; Martos, V.; Santos, E.; Menéndez, M.; Bo, C.; Giralt, E.; de Mendoza, J. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Schmuck, C. (Chem. Commun., 1999)

(untitled) - Gigante, A.; Grad, J.-N.; Briels, J.; Bartel, M.; Hoffmann, D.; Ottmann, C.; Schmuck, C. (Chem. Commun., 2019)

(untitled) - Ehlers, M.; Grad, J.-N.; Mittal, S.; Bier, D.; Mertel, M.; Ohl, L.; Bartel, M.; Briels, J.; Heimann, M.; Ottmann, C.; Sanchez-Garcia, E.; Hoffmann, D.; et al. (ChemBioChem, 2018)

(untitled) - Bartsch, L.; Bartel, M.; Gigante, A.; Iglesias-Fernández, J.; Ruiz-Blanco, Y. B.; Beuck, C.; Briels, J.; Toetsch, N.; Bayer, P.; Sanchez-Garcia, E.; Ottmann, C.; Schmuck, C. (ChemBioChem, 2019)

(untitled) - Gigante, A.; Sijbesma, E.; Sánchez-Murcia, P. A.; Hu, X.; Bier, D.; Bäcker, S.; Knauer, S.; Gago, F.; Ottmann, C.; Schmuck, C. (Angew. Chem., Int. Ed., 2020)

(untitled) - Vallet, C.; Aschmann, D.; Beuck, C.; Killa, M.; Meiners, A.; Mertel, M.; Ehlers, M.; Bayer, P.; Schmuck, C.; Giese, M.; Knauer, S. K. (Angew. Chem., Int. Ed., 2020)

(untitled) - Smith, L. C.; Leach, D. G.; Blaylock, B. E.; Ali, O. A.; Urbach, A. R. (J. Am. Chem. Soc., 2015)

(untitled) - Hirani, Z.; Taylor, H. F.; Babcock, E. F.; Bockus, A. T.; Varnado, C. D., Jr; Bielawski, C. W.; Urbach, A. R. (J. Am. Chem. Soc., 2018)

(untitled) - Gamal-Eldin, M. A.; Macartney, D. H. (Org. Biomol. Chem., 2013)

(untitled) - Guagnini, F.; Antonik, P. M.; Rennie, M. L.; O'Byrne, P.; Khan, A. R.; Pinalli, R.; Dalcanale, E.; Crowley, P. B. (Angew. Chem., Int. Ed., 2018)

(untitled) - Guagnini, F.; Engilberge, S.; Ramberg, K. O.; Pérez, J.; Crowley, P. B. (Chem. Commun., 2020)

(untitled) - Wilson, A. J.; Groves, K.; Jain, R. K.; Park, H. S.; Hamilton, A. D. (J. Am. Chem. Soc., 2003)

(untitled) - Groves, K.; Wilson, A. J.; Hamilton, A. D. (J. Am. Chem. Soc., 2004)

(untitled) - Aya, T.; Hamilton, A. D. (Bioorg. Med. Chem. Lett., 2003)

(untitled) - Gradl, S. N.; Felix, J. P.; Isacoff, E. Y.; Garcia, M. L.; Trauner, D. (J. Am. Chem. Soc., 2003)

(untitled) - Zhou, H.; Baldini, L.; Hong, J.; Wilson, A. J.; Hamilton, A. D. (J. Am. Chem. Soc., 2006)

(untitled) - Mineo, P.; Micali, N.; Villari, V.; Donato, M. G.; Scamporrino, E. (Chem. – Eur. J., 2012)

(untitled) - Cheng, Y.; Tsou, L. K.; Cai, J.; Aya, T.; Dutschman, G. E.; Gullen, E. A.; Grill, S. P.; Chen, A. P.-C.; Lindenbach, B. D.; Hamilton, A. D.; Cheng, Y.-c. (Antimicrob. Agents Chemother., 2010)

(untitled) - Crowley, P. B.; Ganji, P.; Ibrahim, H. (ChemBioChem, 2008)

(untitled) - Kokhan, O.; Ponomarenko, N.; Pokkuluri, P. R.; Schiffer, M.; Tiede, D. M. (Biochemistry, 2014)

(untitled) - Yamaguchi, Y.; Kato, N.; Azuma, H.; Nagasaki, T.; Ohkanda, J. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Wilson, A. J.; Ault, J. R.; Filby, M. H.; Philips, H. I. A.; Ashcroft, A. E.; Fletcher, N. C. (Org. Biomol. Chem., 2013)

(untitled) - Hewitt, S. H.; Filby, M. H.; Hayes, E.; Kuhn, L. T.; Kalverda, A. P.; Webb, M. E.; Wilson, A. J. (ChemBioChem, 2017)

(untitled) - Checco, J. W.; Gellman, S. H. (Curr. Opin. Struct. Biol., 2016)

(untitled) - Jewginski, M.; Fischer, L.; Colombo, C.; Huc, I.; Mackereth, C. D. (ChemBioChem, 2016)

(untitled) - Bartus, É.; Hegedüs, Z.; Wéber, E.; Csipak, B.; Szakonyi, G.; Martinek, T. A. (ChemistryOpen, 2017)

(untitled) - Reddy, P. S.; Langlois d'Estaintot, B.; Granier, T.; Mackereth, C. D.; Fischer, L.; Huc, I. (Chem. – Eur. J., 2019)

(untitled) - Nishino, H.; Huang, C.-S.; Shea, K. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Gao, J.; Tian, H.; Wang, Y.; Yang, Q.; Liu, D.; Wang, Y.; Mi, H. (Biomaterials, 2012)

(untitled) - Canfarotta, F.; Poma, A.; Guerreiro, A.; Piletsky, S. (Nat. Protoc., 2016)

(untitled) - Zhu, X.; Li, H.; Liu, H.; Peng, W.; Zhong, S.; Wang, Y. (J. Sep. Sci., 2016)

(untitled) - Zhang, K.; Zhou, T.; Ye, L.; Bülow, L. (Adv. Exp. Med. Biol., 2017)

(untitled) - Dernedde, J.; Rausch, A.; Weinhart, M.; Enders, S.; Tauber, R.; Licha, K.; Schirner, M.; Zügel, U.; von Bonin, A.; Haag, R. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Zhang, X.; Zhang, Z.; Xu, X.; Li, Y.; Li, Y.; Jian, Y.; Gu, Z. (Angew. Chem., Int. Ed., 2015)

(untitled) - Bayer, E.; Goettsch, S.; Mueller, J. W.; Griewel, B.; Guiberman, E.; Mayr, L. M.; Bayer, P. (J. Biol. Chem., 2003)

(untitled) - Di Costanzo, L.; Geremia, S. (Molecules, 2020)

(untitled) - Engilberge, S.; Riobé, F.; Di Pietro, S.; Lassalle, L.; Coquelle, N.; Arnaud, C.-A.; Pitrat, D.; Mulatier, J.-C.; Madern, D.; Breyton, C.; Maury, O.; Girard, E. (Chem. Sci., 2017)

(untitled) - Engilberge, S.; Riobé, F.; Wagner, T.; Di Pietro, S.; Breyton, C.; Franzetti, B.; Shima, S.; Girard, E.; Dumont, E.; Maury, O. (Chem. – Eur. J., 2018)

(untitled) - Engilberge, S.; Wagner, T.; Santoni, G.; Breyton, C.; Shima, S.; Franzetti, B.; Riobé, F.; Maury, O.; Girard, E. (J. Appl. Crystallogr., 2019)

(untitled) - Hogeweg, A.; Sowislok, A.; Schrader, T.; Beuck, C. (Angew. Chem., Int. Ed., 2017)

(untitled) - Despres, C.; Di, J.; Cantrelle, F.-X.; Li, Z.; Huvent, I.; Chambraud, B.; Zhao, J.; Chen, J.; Chen, S.; Lippens, G.; Zhang, F.; Linhardt, R.; et al. (ACS Chem. Biol., 2019)

(untitled) - Mallon, M.; Dutt, S.; Schrader, T.; Crowley, P. B. (ChemBioChem, 2016)

(untitled) - Williamson, M. P. (Prog. Nucl. Magn. Reson. Spectrosc., 2013)

(untitled) - Kovrigin, E. L. (J. Biomol. NMR, 2012)

(untitled) - Liu, S.; Ruspic, C.; Mukhopadhyay, P.; Chakrabarti, S.; Zavalij, P. Y.; Isaacs, L. (J. Am. Chem. Soc., 2005)

(untitled) - Gossert, A. D.; Jahnke, W. (Prog. Nucl. Magn. Reson. Spectrosc., 2016)

(untitled) - Sugiki, T.; Furuita, K.; Fujiwara, T.; Kojima, C. (Molecules, 2018)

(untitled) - Maity, S.; Gundampati, R. K.; Kumar, T. K. S. (Nat. Prod. Commun., 2019)

(untitled) - Walpole, S.; Monaco, S.; Nepravishta, R.; Angulo, J. (Methods Enzymol., 2019)

(untitled) - Huang, R.; Leung, I. K. H. (Methods Enzymol., 2019)

Modern Magnetic Resonance - Williamson, M. P. (Transferred NOE, 2008)

(untitled) - Kay, L. E.; Torchia, D. A.; Bax, A. (Biochemistry, 1989)

(untitled) - Pervushin, K.; Riek, R.; Wider, G.; Wüthrich, K. (Proc. Natl. Acad. Sci. U. S. A., 1997)

(untitled) - Schanda, P.; Kupče, Ē.; Brutscher, B. (J. Biomol. NMR, 2005)

(untitled) - Favier, A.; Brutscher, B. (J. Biomol. NMR, 2011)

(untitled) - Solyom, Z.; Schwarten, M.; Geist, L.; Konrat, R.; Willbold, D.; Brutscher, B. (J. Biomol. NMR, 2013)

(untitled) - Ayed, A.; Mulder, F. A. A.; Yi, G.-S.; Lu, Y.; Kay, L. E.; Arrowsmith, C. H. (Nat. Struct. Biol., 2001)

(untitled) - Hill, A. V. (J. Physiol., 1910)

(untitled) - Weiss, J. N. (FASEB J., 1997)

(untitled) - Joo, Y.; Schumacher, B.; Landrieu, I.; Bartel, M.; Smet‐Nocca, C.; Jang, A.; Choi, H. S.; Jeon, N. L.; Chang, K.-A.; Kim, H.-S.; Ottmann, C.; Suh, Y.-H. (FASEB J., 2015)

(untitled) - Milroy, L.-G.; Bartel, M.; Henen, M. A.; Leysen, S.; Adriaans, J. M. C.; Brunsveld, L.; Landrieu, I.; Ottmann, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Andrei, S. A.; Meijer, F. A.; Neves, J. F.; Brunsveld, L.; Landrieu, I.; Ottmann, C.; Milroy, L.-G. (ACS Chem. Neurosci., 2018)

(untitled) - Neves, J. F.; Landrieu, I.; Merzougui, H.; Boll, E.; Hanoulle, X.; Cantrelle, F.-X. (Biomol. NMR Assignments, 2019)

(untitled) - Guillory, X.; Wolter, M.; Leysen, S.; Neves, J. F.; Kuusk, A.; Genet, S.; Somsen, B.; Morrow, J. K.; Rivers, E.; van Beek, L.; Patel, J.; Goodnow, R.; et al. (J. Med. Chem., 2020)

(untitled) - Wolter, M.; de Vink, P.; Neves, J. F.; Srdanović, S.; Higuchi, Y.; Kato, N.; Wilson, A.; Landrieu, I.; Brunsveld, L.; Ottmann, C. (J. Am. Chem. Soc., 2020)

(untitled) - Bosica, F.; Andrei, S. A.; Neves, J. F.; Brandt, P.; Gunnarsson, A.; Landrieu, I.; Ottmann, C.; O'Mahony, G. (Chem. – Eur. J., 2020)

(untitled) - Valenti, D.; Neves, J. F.; Cantrelle, F.-X.; Hristeva, S.; Lentini Santo, D.; Obšil, T.; Hanoulle, X.; Levy, L. M.; Tzalis, D.; Landrieu, I.; Ottmann, C. (Med. Chem. Commun., 2019)

(untitled) - O’Grady, C.; Rempel, B. L.; Sokaribo, A.; Nokhrin, S.; Dmitriev, O. Y. (Anal. Biochem., 2012)

(untitled) - Sibille, N.; Huvent, I.; Fauquant, C.; Verdegem, D.; Amniai, L.; Leroy, A.; Wieruszeski, J.-M.; Lippens, G.; Landrieu, I. (Proteins: Struct., Funct., Bioinf., 2012)

(untitled) - Marcotte, D.; Zeng, W.; Hus, J.-C.; McKenzie, A.; Hession, C.; Jin, P.; Bergeron, C.; Lugovskoy, A.; Enyedy, I.; Cuervo, H.; Wang, D.; Atmanene, C.; et al. (Bioorg. Med. Chem., 2013)

(untitled) - Tong, K. I.; Yamamoto, M.; Tanaka, T. (J. Biomol. NMR, 2008)

(untitled) - Duan, G.; Walther, D. (PLoS Comput. Biol., 2015)

(untitled) - Walsh, C. T.; Garneau-Tsodikova, S.; Gatto, G. J., Jr (Angew. Chem., Int. Ed., 2005)

(untitled) - Iwahara, J.; Jung, Y.-S.; Clore, G. M. (J. Am. Chem. Soc., 2007)

(untitled) - Zandarashvili, L.; Esadze, A.; Iwahara, J. (Adv. Protein Chem. Struct. Biol., 2013)

(untitled) - Esadze, A.; Zandarashvili, L.; Iwahara, J. (J. Biomol. NMR, 2014)

(untitled) - Kay, L. E.; Gardner, K. H. (Curr. Opin. Struct. Biol., 1997)

(untitled) - Tugarinov, V.; Hwang, P. M.; Ollerenshaw, J. E.; Kay, L. E. (J. Am. Chem. Soc., 2003)

(untitled) - Ollerenshaw, J. E.; Tugarinov, V.; Kay, L. E. (Magn. Reson. Chem., 2003)

(untitled) - Wiesner, S.; Sprangers, R. (Curr. Opin. Struct. Biol., 2015)

(untitled) - Schuetz, S.; Sprangers, R. (Prog. Nucl. Magn. Reson. Spectrosc., 2020)

(untitled) - Goto, N. K.; Kay, L. E. (Curr. Opin. Struct. Biol., 2000)

(untitled) - Kerfah, R.; Plevin, M. J.; Sounier, R.; Gans, P.; Boisbouvier, J. (Curr. Opin. Struct. Biol., 2015)

(untitled) - Schuetz, A. K.; Kay, L. E. (eLife, 2016)

(untitled) - Bessa, L. M.; Launay, H.; Dujardin, M.; Cantrelle, F.-X.; Lippens, G.; Landrieu, I.; Schneider, R.; Hanoulle, X. (J. Biol. Chem., 2017)

(untitled) - Stoffregen, M. C.; Schwer, M. M.; Renschler, F. A.; Wiesner, S. (Structure, 2012)